Nickel-cobalt-aluminum precursor with two-phase structure as well as preparation method and application of nickel-cobalt-aluminum precursor
By using a nickel-cobalt-aluminum precursor with a two-phase structure, the problem of insufficient doping of Al element in the synthesis of nickel-cobalt-aluminate ternary material is solved, the tap density and electrochemical properties of the material are improved, and the batch stability is enhanced.
Patent Information
- Application Number
- CN202311112202.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-30
- Publication Date
- 2025-02-28
AI Technical Summary
The existing nickel-cobalt lithium aluminate ternary materials are prone to form γ-LiAlO2 or β-LiAlO2 phases during the synthesis process, making it difficult for Al elements to be doped into the main crystal structure, resulting in poor batch stability of the material and unstable discharge specific capacity.
A nickel-cobalt-aluminum precursor with a two-phase structure is used, which consists of nickel-cobalt hydroxide and secondary particles of Al(OH)3. A material containing nickel-cobalt source, cobalt source and Al(OH)3 nanoparticles is contacted with an alkali solution and an ammonia aqueous solution under stirring conditions to form a precursor with high tap density and uniform particle size.
The tap density and electrochemical properties of nickel-cobalt lithium aluminate ternary material are improved, the batch stability of the material is enhanced, and the difficulty of pH control during synthesis is reduced.
Smart Images

Figure CN119542412A_ABST
Abstract
Description
Technical Field
[0001] The present disclosure relates to the technical field of lithium-ion battery positive electrode material precursors, and in particular to a nickel-cobalt-aluminum precursor with a two-phase structure, and a preparation method and application thereof. Background Art
[0002] Nickel cobalt aluminum oxide (NCA) has the advantages of high energy density, long cycle life, and good safety performance, and has been widely used in the field of power batteries for electric vehicles. In the preparation of NCA ternary materials, the precursor is one of the most critical factors affecting product performance. At present, the synthesis of NCA mainly includes two process routes.
[0003] One process route is to first directly prepare the nickel-cobalt-aluminum precursor by coprecipitation, and then mix it with lithium salt and calcine it to obtain NCA material. 3 The solubility product constant is 1.3×10 -33 , while Ni(OH) 2 and Co(OH) 2 2×10 -15 and 1.6×10 -15 In addition, Al 3+ It is difficult to communicate with NH 3 Complexation reaction occurs, so when the nickel-cobalt-aluminum precursor is prepared by conventional chemical precipitation, Al 3+ The precipitation speed is very fast, and flocculent precipitation is easily formed, resulting in poor sphericity, small particle size, loose structure and low tap density of the prepared precursor; and Al(OH) 3 As an amphoteric hydroxide, the pH value must be controlled with high precision during the reaction, and the synthesis technology is difficult.
[0004] Another process route is to prepare a nickel-cobalt hydroxide precursor by coprecipitation, and then mix it with aluminum oxide or hydroxide and lithium salt and calcine it to obtain a nickel-cobalt-aluminum-lithium ternary material. The advantage of this process is that the precursor synthesis is easy and it is easy to synthesize a NCA ternary material with large particle size and high tap density. 2 O 3 or Al(OH) 3 γ-LiAlO is easily produced during the lithiation roasting process. 2 or β-LiAlO 2 phase, making it difficult for some Al to be doped into the main crystal structure, resulting in poor batch stability and unstable discharge specific capacity of the prepared NCA material.
[0005] Chinese invention patent ZL 202010416056.0 discloses a method for preparing a nickel cobalt aluminum oxide positive electrode material. The patent first prepares spherical nickel hydroxide and cobalt aluminum hydrotalcite nanosheets separately, and then coats the cobalt aluminum hydrotalcite nanosheets on the surface of the spherical nickel hydroxide by solid phase ball milling. The cobalt aluminum hydrotalcite nanosheets coated with spherical nickel hydroxide are used as a precursor and mixed with lithium compounds for calcination to obtain a nickel cobalt aluminum oxide positive electrode material. This method utilizes the synergistic diffusion effect of Co and Al, so that Co and Al can be incorporated into the crystal structure at the same time, avoiding the γ-LiAlO 2 or β-LiAlO 2 The formation of solid phase can achieve uniform distribution of nickel, cobalt and aluminum. However, the uniformity of solid phase coating is poor, and the electrochemical performance of the synthesized NCA ternary material is unstable. Summary of the invention
[0006] The purpose of the present disclosure is to provide a nickel-cobalt-aluminum precursor with a two-phase structure, a preparation method and an application thereof. The nickel-cobalt-aluminum precursor has a large particle size and a high tap density. Using it to prepare nickel-cobalt-aluminum lithium oxide ternary materials can improve the tap density and electrochemical properties, and can improve the batch stability of the material.
[0007] In order to achieve the above-mentioned object, the present disclosure provides a nickel-cobalt-aluminum precursor having a two-phase structure in the first aspect, wherein the nickel-cobalt-aluminum precursor comprises nickel-cobalt hydroxide and Al(OH) 3 of secondary particles.
[0008] Optionally, the nickel-cobalt hydroxide has a β crystal form;
[0009] The chemical formula of the nickel cobalt hydroxide is Ni 1-x Co x (OH) 2 , 0.05≤x≤0.2.
[0010] Optionally, in the XRD spectrum of the nickel-cobalt-aluminum precursor, there is Al(OH) 3 Characteristic peaks of crystals and characteristic peaks of nickel cobalt hydroxide crystals.
[0011] Optionally, the secondary particles have Al(OH) 3 A two-phase microscopic crystal structure in which the crystals are dispersed in nickel-cobalt hydroxide crystals.
[0012] Optionally, the tap density of the secondary particles is 1.90 g / cm 3 Above, the specific surface area is 6-25m 2 / g, D50 is 8-15μm.
[0013] Optionally, in the nickel-cobalt-aluminum precursor, the molar ratio of aluminum element to metal element is (0.02-0.09):1.
[0014] The second aspect of the present disclosure provides a method for preparing a nickel-cobalt-aluminum precursor, the method comprising: mixing a mixture containing a nickel source, a cobalt source and Al(OH) 3 The first material of nanoparticles, the first alkaline solution and the ammonia solution undergo a first contact reaction;
[0015] The Al(OH) 3 The D50 of nanoparticles is 10-50nm;
[0016] The first contact reaction is carried out under the condition that the pH value measured at a liquid temperature of 50° C. is 10.5-11.0.
[0017] Optionally, the method for preparing the first material comprises: mixing the Al(OH) 3 The suspension of nanoparticles is mixed with a solution containing the nickel source and the cobalt source;
[0018] Optionally, the solid content of the suspension is 10-30% by weight;
[0019] Optionally, the total concentration of cobalt ions and nickel ions in the solution is 1.5-2.5 mol / L;
[0020] Optionally, in the first material, the molar ratio of aluminum element to metal element is (0.02-0.09):1.
[0021] Optionally, the nickel source includes nickel sulfate and / or nickel chloride;
[0022] The cobalt source includes cobalt sulfate and / or cobalt chloride.
[0023] Optionally, the first alkaline solution contains sodium hydroxide and / or potassium hydroxide;
[0024] The concentration of the first alkaline solution is 4-10 mol / L, and the mass fraction of the ammonia solution is 15-22%.
[0025] Optionally, the method comprises the following steps:
[0026] a. Add water, a portion of the first alkaline solution and a portion of the ammonia solution into a reaction kettle under stirring;
[0027] The total volume of the water, a portion of the first alkaline solution and a portion of the ammonia solution accounts for 30-80% of the volume fraction of the reactor;
[0028] b. Adding the first material, another part of the first alkali solution and another part of the ammonia solution into the reactor of step a under stirring to carry out the first contact reaction, and stopping feeding when the D50 of the solid material in the reactor is 8-15 μm;
[0029] The first material, another part of the first alkaline solution and another part of the ammonia solution are added for 80-200 hours;
[0030] When the volume of the material in the reactor accounts for 80%-85% of the total volume of the reactor, the clear liquid is discharged out of the reactor through a concentrator.
[0031] Optionally, in step a, in the solution in the reactor, NH 3 The concentration is 3-10 g / L, the pH value of the solution in the reactor is 10.5-11.0 when measured at a liquid temperature of 50° C., and the stirring power density of the solution is 3-9 W / L;
[0032] In step b, in the slurry in the reactor, NH 3 The concentration is 3-10 g / L; the pH value of the slurry in the reactor is 10.5-11.0 when measured at a liquid temperature of 50° C., and the stirring power density of the slurry is 3-9 W / L;
[0033] The temperature of the first contact reaction is 50-65°C.
[0034] Optionally, the method further comprises: performing alkaline washing on the second material obtained by the first contact reaction, wherein the alkaline washing comprises: washing the second material with water, a second alkaline solution and water in sequence until the pH value of the washing solution is below 8.0;
[0035] The second alkaline solution contains sodium hydroxide and / or potassium hydroxide, the concentration of the second alkaline solution is 1-2% by weight, and the total time of the alkaline washing is 1-3 hours;
[0036] Optionally, the method further comprises: drying the third material obtained by the alkali washing, and the conditions of the drying process comprise: a time of 5-12 hours and a temperature of 100-150°C.
[0037] The third aspect of the present disclosure provides a nickel-cobalt-aluminum precursor having a two-phase structure prepared by the method described in the second aspect of the present disclosure.
[0038] A fourth aspect of the present disclosure provides a method for preparing a nickel-cobalt-aluminum-lithium ternary material, the method comprising:
[0039] The nickel-cobalt-aluminum precursor described in the first aspect or the third aspect of the present disclosure is mixed with a lithium source and then heat-treated in an oxygen-containing atmosphere.
[0040] Optionally, the lithium source includes one or more of lithium carbonate, lithium hydroxide, lithium acetate, lithium oxalate and lithium nitrate;
[0041] The molar ratio of the lithium source calculated as lithium element to the nickel-cobalt-aluminum precursor calculated as metal element is (1.01-1.06):1;
[0042] Optionally, the mixing method is solid phase ball milling, and the solid phase ball milling time is 1-5 hours.
[0043] Optionally, the heat treatment conditions include: time of 8-20h and temperature of 650-850°C.
[0044] The fifth aspect of the present disclosure provides a nickel-cobalt-aluminum-lithium oxide ternary material prepared by the method described in the fourth aspect of the present disclosure.
[0045] Optionally, the tap density of the nickel-cobalt-aluminum-lithium oxide ternary material is 2.3 g / cm 3 Above, D50 is 8-15μm.
[0046] A sixth aspect of the present disclosure provides a lithium-ion battery, the lithium-ion battery comprising a positive electrode, an electrolyte and a negative electrode, the positive electrode comprising the nickel-cobalt-aluminum-lithium ternary material described in the fifth aspect of the present disclosure.
[0047] Through the above technical solution, the present invention is to prepare Al(OH) 3 The nanoparticles are mixed with a solution containing a nickel source and a cobalt source, and precipitated under specific pH conditions to form a nickel-cobalt-aluminum precursor with a two-phase structure. The method disclosed in the present invention overcomes the technical difficulties that aluminum hydroxide flocculent precipitation is produced when directly precipitating and synthesizing nickel-cobalt-aluminum hydroxide by conventional liquid phase method, resulting in the inability to grow the particle size and low tap density; the Al element in the nickel-cobalt-aluminum precursor disclosed in the present invention is in the form of Al(OH) 3 The nickel-cobalt-aluminum precursor can be used as a precursor for synthesizing a nickel-cobalt-aluminum-oxide ternary positive electrode material. When the nickel-cobalt-aluminum precursor disclosed in the present invention is used to synthesize a nickel-cobalt-aluminum-oxide ternary positive electrode material, the Al element can be prevented from generating γ-LiAlO. 2 or β-LiAlO 2 The phase, which causes the technical difficulty of partial Al being difficult to be doped into the main crystal structure, can improve the tap density and electrochemical properties of NCA ternary materials, and more importantly, improve the batch stability of the material; and the synthesis method disclosed in the present invention has a wide pH value control range and is simple to operate, which reduces the control difficulty of industrial production.
[0048] Other features and advantages of the present disclosure will be described in detail in the following detailed description. BRIEF DESCRIPTION OF THE DRAWINGS
[0049] The accompanying drawings are used to provide a further understanding of the present disclosure and constitute a part of the specification. Together with the following specific embodiments, they are used to explain the present disclosure but do not constitute a limitation of the present disclosure. In the accompanying drawings:
[0050] Figure 1 This is the XRD pattern of the nickel-cobalt-aluminum precursor A1 prepared in Example 1 of the present disclosure.
[0051] Figure 2 This is the XRD diagram of the nickel-cobalt-aluminum precursor D1 prepared in Comparative Example 1 of the present disclosure.
[0052] Figure 3 This is a SEM image of the nickel-cobalt-aluminum precursor A1 prepared in Example 1 of the present disclosure.
[0053] Figure 4 This is a SEM image of the nickel-cobalt-aluminum precursor D1 prepared in Comparative Example 1 of the present disclosure.
[0054] Figure 5 This is a SEM image of the nickel-cobalt precursor D2 prepared in Comparative Example 2 of the present disclosure.
[0055] Figure 6 This is the particle size distribution diagram of the nickel-cobalt-aluminum precursor A1 prepared in Example 1 of the present disclosure.
[0056] Figure 7 XRD curves of the nickel cobalt aluminum oxide ternary materials A1-1, D1-1 and D2-1 prepared in Preparation Example 1, Comparative Example 1 and Comparative Example 2 of the present disclosure. DETAILED DESCRIPTION
[0057] The specific implementation of the present disclosure is described in detail below in conjunction with the accompanying drawings. It should be understood that the specific implementation described herein is only used to illustrate and explain the present disclosure, and is not used to limit the present disclosure.
[0058] The present disclosure provides a nickel-cobalt-aluminum precursor having a two-phase structure, wherein the nickel-cobalt-aluminum precursor comprises nickel-cobalt hydroxide and Al(OH) 3 of secondary particles.
[0059] According to one embodiment of the present disclosure, in the XRD spectrum of the nickel-cobalt-aluminum precursor having a two-phase structure, there is Al(OH) 3 The characteristic peaks of the crystal and the characteristic peaks of the nickel cobalt hydroxide crystal; further, the secondary particles have Al(OH) 3The nickel-cobalt-aluminum precursor of the present invention has a two-phase microscopic crystal structure in which the nickel-cobalt-hydroxide crystals are dispersed in the nickel-cobalt-hydroxide crystals; According to the above characteristics, it can be known that the nickel-cobalt-aluminum precursor disclosed in the present invention has a two-phase structure, namely, a crystalline phase of nickel-cobalt-hydroxide and Al(OH) 3 The two primary particles form secondary particles, which may be spherical and / or quasi-spherical. The meanings of spherical, quasi-spherical and secondary particles are known in the art. The nickel-cobalt-aluminum precursor with a two-phase structure disclosed in the present invention has a large particle size and a high tap density, which can improve the tap density and electrochemical properties of the nickel-cobalt-aluminum lithium oxide ternary positive electrode material (NCA), and can improve the batch stability of the material.
[0060] According to one embodiment of the present disclosure, the nickel cobalt hydroxide has a β crystal form, which can be tested by XRD; the chemical formula of the nickel cobalt hydroxide is Ni 1-x Co x (OH) 2 , 0.05≤x≤0.2, preferably, 0.05≤x≤0.15.
[0061] According to one embodiment of the present disclosure, the tap density of the secondary particles is 1.90 g / cm 3 Above, D50 is 8-15μm, specific surface area is 6-25m 2 / g; The nickel-cobalt-aluminum precursor with the above structural characteristics can improve the tap density and electrochemical properties of NCA when preparing NCA.
[0062] According to one embodiment of the present disclosure, in the nickel-cobalt-aluminum precursor, the molar ratio of aluminum element to metal element is (0.02-0.09):1, preferably (0.02-0.05):1.
[0063] The second aspect of the present disclosure provides a method for preparing a nickel-cobalt-aluminum precursor having a two-phase structure, the method comprising: mixing a nickel source, a cobalt source and Al(OH) 3 The first material of nanoparticles, the first alkaline solution and the ammonia solution undergo a first contact reaction;
[0064] The Al(OH) 3 The D50 of nanoparticles is 10-50nm;
[0065] The first contact reaction is carried out under the condition that the pH value measured at a liquid temperature of 50° C. is 10.5-11.0.
[0066] The method disclosed in the present invention overcomes the technical difficulty that aluminum hydroxide flocculent precipitation is produced when the conventional liquid phase method is used to directly precipitate and synthesize nickel-cobalt-aluminum hydroxide, resulting in the inability to grow the particle size and low tap density; on the other hand, it also overcomes the problem that when a nickel-cobalt hydroxide precursor is first synthesized and then mixed with aluminum oxide or hydroxide and lithium salt and then calcined to prepare a nickel-cobalt-aluminum-lithium oxide ternary material, the Al element generates γ-LiAlO 2 or β-LiAlO 2 phase, resulting in the technical difficulty of some Al being difficult to dope into the main crystal structure.
[0067] In the present disclosure, "pH value measured at a liquid temperature of 50° C." refers to a pH value measured at a temperature of 50° C. and a standard atmospheric pressure.
[0068] According to one embodiment of the present disclosure, the method for preparing the first material comprises: mixing the Al(OH) 3 The suspension of nanoparticles is mixed with a solution containing the nickel source and the cobalt source; a solution containing Al(OH) 3 The method for preparing the suspension of nanoparticles may include, for example, preparing Al(OH) 3 Mix with water, and grind the obtained mixture to form a mixture containing Al(OH) 3 The suspension of nanoparticles was crushed by sand milling for 2-5h at a speed of 2500-3000r / min. The prepared suspension was kept in a stirring state to avoid Al(OH) 3 The suspension settles to the bottom of the container; the solid content of the suspension is 10-30% by weight.
[0069] According to one embodiment of the present disclosure, the total concentration of cobalt ions and nickel ions in the solution is 1.5-2.5 mol / L; the amount of nickel source and cobalt source is set according to the ratio of Co to Ni in the desired product.
[0070] According to one embodiment of the present disclosure, in the first material, the molar ratio of aluminum element to metal element is (0.02-0.09):1, preferably (0.02-0.05):1.
[0071] According to one embodiment of the present disclosure, the types of nickel source and cobalt source are conventional in the art. The nickel source may be, for example, a soluble salt of nickel, and the cobalt source may be, for example, a soluble salt of cobalt. Specifically, the nickel source includes nickel sulfate and / or nickel chloride; the cobalt source includes cobalt sulfate and / or cobalt chloride. When the nickel source and / or cobalt source include more than two substances, the present disclosure does not impose specific restrictions on their ratio.
[0072] According to one embodiment of the present disclosure, the first alkaline solution contains sodium hydroxide and / or potassium hydroxide, and the concentration of the first alkaline solution is 4-10 mol / L.
[0073] According to one embodiment of the present disclosure, the mass fraction of the ammonia solution is 15-22%.
[0074] According to one embodiment of the present disclosure, the method comprises the following steps:
[0075] a. Add water, a portion of the first alkaline solution and a portion of the ammonia solution into a reaction kettle under stirring;
[0076] The total volume of the water, a portion of the first alkaline solution and a portion of the ammonia solution accounts for 30-80% of the volume fraction of the reactor;
[0077] b. Adding the first material, another part of the first alkali solution and another part of the ammonia solution into the reactor of step a under stirring to carry out the first contact reaction, and stopping feeding when the D50 of the solid material in the reactor is 8-15 μm;
[0078] The first material, another part of the first alkali solution and another part of the ammonia solution are added for 80-200 hours, and the first material, another part of the first alkali solution and another part of the ammonia solution are preferably added at the same time;
[0079] When the volume of the material in the reactor accounts for 80-85% of the total volume of the reactor, the clear liquid is discharged from the reactor through a concentrator.
[0080] According to one embodiment of the present disclosure, in step a, in the solution in the reactor, NH 3 The concentration is 3-10 g / L, the pH value of the solution in the reactor is 10.5-11.0 measured based on a liquid temperature of 50° C., and the stirring power density of the solution is 3-9 W / L.
[0081] According to one embodiment of the present disclosure, in step b, in the slurry in the reactor, NH 3 The concentration is 3-10 g / L; the pH value of the slurry in the reactor is 10.5-11.0 measured based on a liquid temperature of 50° C., and the stirring power density of the slurry is 3-9 W / L.
[0082] According to one embodiment of the present disclosure, in step a and step b, the pH value of the solution in the reaction kettle is the same as that of the slurry in the reaction kettle.
[0083] In the present disclosure, in step b, the pH value of the slurry in the reactor is controlled by controlling the addition rate of the first alkaline solution, NH 3 The concentration is controlled by the rate of introduction of ammonia solution.
[0084] In the present disclosure, the adding rate of the first material in step b is conventional in the art.
[0085] According to one embodiment of the present disclosure, the temperature of the first contact reaction is 50-65°C.
[0086] According to one embodiment of the present disclosure, in order to further remove anions such as sulfate and chloride ions in the product, the method further includes: performing alkaline washing on the second material obtained by the first contact reaction, and the steps and conditions of the alkaline washing are conventional in the art, for example, may include: washing the second material with water, a second alkaline solution and water in sequence until the pH value of the washing liquid is below 8.0 (test value under standard atmospheric pressure of 25°C); the second alkaline solution contains sodium hydroxide and / or potassium hydroxide, the concentration of the second alkaline solution is 1-2% by weight, and the total time of the alkaline washing is 1-3h.
[0087] According to an embodiment of the present disclosure, the method further comprises: drying the third material obtained by the alkali washing, and the conditions of the drying treatment comprise: a time of 5-12 hours and a temperature of 100-150°C.
[0088] The third aspect of the present disclosure provides a nickel-cobalt-aluminum precursor having a two-phase structure prepared by the method described in the second aspect of the present disclosure.
[0089] The nickel-cobalt-aluminum precursor with a two-phase structure described in the third aspect of the present disclosure has the same characteristics as the nickel-cobalt-aluminum precursor with a two-phase structure described in the first aspect of the present disclosure, and will not be elaborated here.
[0090] A fourth aspect of the present disclosure provides a method for preparing a nickel-cobalt-aluminum-lithium ternary material, the method comprising:
[0091] The nickel-cobalt-aluminum precursor described in the first aspect or the third aspect of the present disclosure is mixed with a lithium source and then heat-treated in an oxygen-containing atmosphere.
[0092] According to one embodiment of the present disclosure, the lithium source includes one or more of lithium carbonate, lithium hydroxide, lithium acetate, lithium oxalate and lithium nitrate; the molar ratio of the lithium source calculated as lithium element to the nickel-cobalt-aluminum precursor calculated as metal element is (1.01-1.06):1.
[0093] According to one embodiment of the present disclosure, the mixing method is solid phase ball milling, and the solid phase ball milling time is 1-5 hours.
[0094] According to one embodiment of the present disclosure, the heat treatment conditions include: a time of 8-20 hours and a temperature of 650-850°C.
[0095] The fifth aspect of the present disclosure provides a method for preparing a nickel-cobalt-aluminum-lithium ternary material using the method described in the fourth aspect of the present disclosure.
[0096] According to one embodiment of the present disclosure, the chemical formula of the nickel-cobalt-aluminum-lithium oxide ternary material is Li 1+δ Ni 1-a- b Co a Al b O 2 , among which, 0.05≤a≤0.2, 0.02≤b≤0.09, 0.01≤δ≤0.06.
[0097] According to one embodiment of the present disclosure, the tap density of the nickel-cobalt-aluminum-lithium oxide ternary material is 2.3 g / cm 3 Above, D50 is 8-15μm.
[0098] A sixth aspect of the present disclosure provides a lithium-ion battery, the lithium-ion battery comprising a positive electrode, an electrolyte and a negative electrode, the positive electrode comprising the nickel-cobalt-aluminum-lithium ternary material described in the fifth aspect of the present disclosure.
[0099] In the present disclosure, the types of negative electrodes and electrolytes of lithium-ion batteries are conventional in the art, and no specific requirements are made herein, as long as the solutions of the present disclosure can be implemented.
[0100] The present invention will be described in detail below in conjunction with specific embodiments. The following embodiments will help those skilled in the art to further understand the present invention, but are not intended to limit the present invention in any form.
[0101] The raw materials used in the examples were all purchased from commercial sources and were of analytical grade unless otherwise specified.
[0102] XRD test conditions and instrument model: Equipment model: Japanese UItima-III XX-ray powder diffractometer. Test conditions: Cu target Kα light source, wavelength λ=0.154nm, scanning speed of 5° / min, scanning range 2θ of 10-80°, step length of 0.04°.
[0103] SEM test conditions and instrument model: Equipment model: FEIQuanta 400 scanning electron microscope; Test conditions: test voltage is 5kV.
[0104] The test method and instrument model of tap density: Equipment model: Dandong Better BT-300 tap density tester. Test conditions: sample 100g, amplitude 3mm, vibration frequency 300 times / min, test time 5min.
[0105] The particle size test instrument model: Mastersizer 2000 laser particle size distribution analyzer produced by Malvern. The test conditions are: particle refractive index 2.16, particle absorption rate 0.1, dispersant is deionized water, dispersant refractive index 1.330, shading degree 5%-10%, and analysis mode is general.
[0106] The molar ratio of aluminum element to metal element in the nickel-cobalt-aluminum precursor is the same as the feed ratio.
[0107] Example 1
[0108] The nickel-cobalt-aluminum precursor A1 was prepared by the following steps:
[0109] (1) 21.97 kg of NiSO 4 6H 2 O and 4.54 kg of CoSO 4 7H 2 O was dissolved in deionized water to prepare a solution with a total volume of 50 L;
[0110] 487.5 g of Al(OH) 3 Add to 4387.5 g of deionized water, grind at 3000 r / min for 5 h to form a 10 wt% solid content Al(OH) 3 A suspension of nanoparticles; containing Al(OH) 3 The suspension of nanoparticles is mixed with a solution containing a nickel source and a cobalt source to obtain a first material; the first material is always in a stirring state to avoid Al(OH) 3 precipitation;
[0111] Contains Al(OH) 3 Al(OH) in suspension 3 The D50 of the nanoparticles is 30 nm;
[0112] 8.4 kg of sodium hydroxide was added to deionized water to prepare 35 L of a first alkaline solution with a concentration of 6 mol / L;
[0113] Add 25% concentrated ammonia water into deionized water to prepare a 15% ammonia water solution;
[0114] (2) adding 3 L of deionized water into a reactor with a volume of 10 L, adding a portion of the first alkali solution and a portion of the ammonia solution as a reaction base solution into the reactor under stirring, and the stirring power density of the solution is 5 W / L;
[0115] The pH value of the reaction solution was 11.0 when the temperature was 50°C. 3 The concentration is 5g / L;
[0116] (3) under stirring conditions, the first material, another part of the first alkali solution and another part of the ammonia solution are added to the reactor in parallel to carry out a first contact reaction at a temperature of 60° C. and a stirring power density of the slurry of 5 W / L;
[0117] The addition time of the first material, another part of the first alkali solution and another part of the ammonia solution is 130 hours;
[0118] In step (3), the rate of addition of aqueous ammonia solution is adjusted so that NH 3 The concentration of the first alkali solution is 5 g / L, and the pH value of the slurry measured at a liquid temperature of 50° C. is 11.0 according to the addition rate of the first alkali solution;
[0119] When the total volume of the material in the reactor reaches 8L, start the diaphragm pump and the concentrator to concentrate the slurry, the concentrated liquid flows back to the reactor, and the clear liquid is discharged into the waste liquid tank;
[0120] When the solid material in the reactor is detected, 50 When the particle size reaches 9 μm, the feeding is stopped to obtain the second material;
[0121] (4) adding the second material into a washing machine, and washing with deionized water, a sodium hydroxide solution with a mass fraction of 1%, and deionized water in sequence for a total time of 3 hours, until the pH value of the washing liquid is below 8.0 (test value at 25° C. standard atmospheric pressure), stopping washing, and obtaining a third material;
[0122] (5) The third material was dried at 120° C. for 10 h. After drying, it was sieved and demagnetized to obtain a nickel-cobalt-aluminum precursor A1, the parameters of which are listed in Table 1.
[0123] The XRD test of NiCoAl precursor A1 was carried out, and the results are as follows Figure 1 As shown, Figure 1 Al(OH) 3 The characteristic peaks of the crystal and the characteristic peaks of the nickel-cobalt hydroxide crystal indicate that the nickel-cobalt-aluminum precursor contains a chemical formula of Ni 0.84 Co 0.16 (OH) 2 NiCoOH and Al(OH) 3 , and the nickel-cobalt hydroxide has a β-crystal form, indicating that the nickel-cobalt-aluminum precursor prepared by the method of the present application has a two-phase structure.
[0124] The SEM test of NiCoAl precursor A1 was carried out, and the results are as follows Figure 3 As shown in the low-magnification electron microscope photo (left), it can be seen that the precursor particles are uniform and there are no small particles, indicating that Al(OH) 3 Doped with Ni0.84 Co 0.16 (OH) 2 Precursor; From the high-power electron microscope photo (right), it can be clearly seen that the precursor particles are composed of Ni with lamellar morphology. 0.84 Co 0.16 (OH) 2 and Al(OH) with granular morphology 3 They are intertwined to form spherical secondary particles.
[0125] The particle size distribution test of nickel-cobalt-aluminum precursor A1 was carried out, and the results are as follows Figure 6 As shown, it can be seen that the particle size distribution has a high concentration, which can also explain the Al(OH) 3 Doped with Ni 0.84 Co 0.16 (OH) 2 middle.
[0126] Example 2
[0127] The nickel-cobalt-aluminum precursor A2 was prepared by the following steps:
[0128] (1) 29.18 kg of NiSO 4 6H 2 O and 3.91 kg of CoSO 4 7H 2 O was dissolved in deionized water to prepare a solution with a total volume of 50 L;
[0129] 847.8 g of Al(OH) 3 Added into 1978.2g of deionized water, and crushed by sand mill at a speed of 2500r / min for 5h to form a 30wt% solid content containing Al(OH) 3 A suspension of nanoparticles; containing Al(OH) 3 The suspension of nanoparticles is mixed with a solution containing a nickel source and a cobalt source to obtain a first material; the first material is always in a stirring state to avoid Al(OH) 3 precipitation;
[0130] Contains Al(OH) 3 Al(OH) in suspension 3 The D50 of the nanoparticles is 30 nm;
[0131] 11.0 kg of sodium hydroxide was added to deionized water to prepare 68 L of a first alkaline solution with a concentration of 4 mol / L;
[0132] Adding 25% concentrated ammonia water into deionized water to prepare a 22% ammonia water solution;
[0133] (2) adding 8 L of deionized water into a reactor with a volume of 10 L, adding a portion of the first alkali solution and a portion of the ammonia solution as a reaction base solution into the reactor under stirring, and the stirring power density of the solution is 5 W / L;
[0134] The pH value of the reaction solution was 10.5 when the temperature was 50℃. 3 The concentration is 4g / L;
[0135] (3) under stirring conditions, the first material, another part of the first alkali solution and another part of the ammonia solution are added to the reactor in parallel to carry out a first contact reaction at a temperature of 50° C. and a stirring power density of the slurry of 5 W / L;
[0136] The addition time of the first material, another part of the first alkali solution and another part of the ammonia solution is 80 hours;
[0137] In step (3), the rate of addition of aqueous ammonia solution is adjusted so that NH 3 The concentration of the first alkali solution is 4 g / L, and the pH value of the slurry measured at a liquid temperature of 50° C. is 10.5 according to the addition rate of the first alkali solution;
[0138] Start the diaphragm pump and the thickener to concentrate the slurry, the concentrated liquid flows back to the reactor, and the clear liquid is discharged into the waste liquid tank;
[0139] When the solid material in the reactor is detected, 50 When the particle size reaches 8 μm, the feeding is stopped to obtain the second material;
[0140] (4) adding the second material into a washing machine, washing with deionized water, a sodium hydroxide solution with a mass fraction of 2 wt % and deionized water in sequence, for a total time of 2 h, until the pH value of the washing liquid is below 8.0 (test value at 25° C. standard atmospheric pressure), stopping washing, and obtaining a third material;
[0141] (5) The third material was dried at 150° C. for 15 h. After drying, it was sieved and demagnetized to obtain a nickel-cobalt-aluminum precursor A2, the parameters of which are listed in Table 1.
[0142] The NiCoAl precursor A2 was tested by XRD. The XRD spectrum showed Al(OH) 3 The characteristic peaks of the crystal and the characteristic peaks of the nickel-cobalt hydroxide crystal indicate that the nickel-cobalt-aluminum precursor contains a chemical formula of Ni 0.89 Co 0.11 (OH) 2 NiCoOH and Al(OH) 3 , and nickel-cobalt hydroxide has a β-crystal form. SEM test shows that it has Al(OH) 3A two-phase microscopic crystal structure in which the crystals are dispersed in nickel-cobalt hydroxide crystals.
[0143] Example 3
[0144] The nickel-cobalt-aluminum precursor A3 was prepared by the following steps:
[0145] (1) 18.55 kg of NiSO 4 6H 2 O and 1.11 kg of CoSO 4 7H 2 O was dissolved in deionized water to prepare a solution with a total volume of 50 L;
[0146] 180.9 g of Al(OH) 3 Add to 723.6 g of deionized water, grind at 3000 r / min for 2 h to form a 20 wt% solid content Al(OH) 3 A suspension of nanoparticles; containing Al(OH) 3 The suspension of nanoparticles is mixed with a solution containing a nickel source and a cobalt source to obtain a first material; in addition, the first material is always in a stirring state to avoid Al(OH) 3 precipitation;
[0147] Contains Al(OH) 3 Al(OH) in suspension 3 The D50 of the nanoparticles is 50 nm;
[0148] 6.6 kg of sodium hydroxide was added to deionized water to prepare 16.5 L of a first alkaline solution with a concentration of 10 mol / L;
[0149] Adding 25% concentrated ammonia water into deionized water to prepare a 15% ammonia water solution;
[0150] (2) adding 5 L of deionized water into a 10 L reactor, adding a portion of the first alkali solution and a portion of the ammonia solution as a reaction base solution into the reactor under stirring, and the stirring power density of the solution is 9 W / L;
[0151] The pH value of the reaction solution was 10.8 when the temperature was 50℃. 3 The concentration is 10g / L;
[0152] (3) under stirring conditions, adding the first material, another part of the first alkali solution and another part of the ammonia solution into the reactor in parallel to carry out a first contact reaction at a temperature of 60° C. and a stirring power density of the slurry of 9 W / L;
[0153] The first material, another part of the first alkali solution and another part of the ammonia solution are added for 200 hours respectively;
[0154] In step (3), the rate of addition of aqueous ammonia solution is adjusted so that NH 3 The concentration of the first alkali solution is 10 g / L, and the pH value of the slurry measured at a liquid temperature of 50° C. is 10.8 according to the addition rate of the first alkali solution;
[0155] When the total volume of the material in the reactor reaches 8L, start the diaphragm pump and the concentrator to concentrate the slurry, the concentrated liquid flows back to the reactor, and the clear liquid is discharged into the waste liquid tank;
[0156] When the solid material in the reactor is detected, 50 When the particle size reaches 12 μm, the feeding is stopped to obtain the second material;
[0157] (4) adding the second material into a washing machine, washing with deionized water, a sodium hydroxide solution with a mass fraction of 2 wt % and deionized water in sequence for 2 h until the pH value of the washing liquid is below 8.0 (test value at 25° C. standard atmospheric pressure), stopping washing, and obtaining a third material;
[0158] (5) The third material was dried at 120° C. for 10 h. After drying, it was sieved and demagnetized to obtain a nickel-cobalt-aluminum precursor A3, the parameters of which are listed in Table 1.
[0159] The nickel-cobalt-aluminum precursor A3 was tested by XRD. The XRD spectrum showed Al(OH) 3 The characteristic peaks of the crystal and the characteristic peaks of the nickel-cobalt hydroxide crystal indicate that the nickel-cobalt-aluminum precursor contains a chemical formula of Ni 0.947 Co 0.053 (OH) 2 NiCoOH and Al(OH) 3 , and nickel-cobalt hydroxide has a β-crystal form. SEM test shows that it has Al(OH) 3 A two-phase microscopic crystal structure in which the crystals are dispersed in nickel-cobalt hydroxide crystals.
[0160] Comparative Example 1
[0161] The nickel-cobalt-aluminum precursor D1 was prepared by the following steps:
[0162] (1) 21.97 kg of NiSO 4 6H 2 O, 4.54 kg of CoSO 4 7H 2 O and 3.54 kg of Al 2 (SO 4 ) 3 18H2 O was dissolved in deionized water to prepare a mixed metal salt solution with a total volume of 50 L and a total metal ion concentration of 2.0 mol / L;
[0163] 8.4 kg of sodium hydroxide was added to deionized water to prepare 35 L of a first alkaline solution with a concentration of 6 mol / L;
[0164] Add 25% concentrated ammonia water into deionized water to prepare a 15% ammonia water solution;
[0165] (2) adding 3 L of deionized water into a reactor with a volume of 10 L, adding a portion of the first alkali solution and a portion of the ammonia solution as a reaction base solution into the reactor under stirring, and the stirring power density of the solution is 5 W / L;
[0166] The pH value of the reaction solution was 11.0 when the temperature was 50°C. 3 The concentration is 5g / L;
[0167] (3) under stirring conditions, adding the mixed metal salt solution prepared in step (1), another part of the first alkali solution and another part of the ammonia solution into the reactor in parallel to carry out a first contact reaction at a temperature of 60° C. and a stirring power density of the slurry of 9 W / L;
[0168] The addition time of the mixed metal salt solution, another part of the first alkali solution and another part of the ammonia solution is 130 hours;
[0169] In step (3), the rate of addition of aqueous ammonia solution is adjusted so that NH 3 The concentration of the first alkali solution is 5 g / L, and the pH value of the slurry measured at a liquid temperature of 50° C. is 11.0 by adjusting the addition rate of the first alkali solution;
[0170] When the total volume of the material in the reactor reaches 8L, start the diaphragm pump and the concentrator to concentrate the slurry, the concentrated liquid flows back to the reactor, and the clear liquid is discharged into the waste liquid tank;
[0171] When the reaction time is the same as step (3) of Example 1, the feeding is stopped to obtain a second material;
[0172] (4) adding the second material into a washing machine, washing with deionized water, a sodium hydroxide solution with a mass fraction of 1%, and deionized water in sequence until the pH value of the washing liquid is below 8.0 (test value at 25° C. standard atmospheric pressure), stopping washing, and obtaining a third material;
[0173] (5) The third material was dried at 120° C. for 10 h. After drying, it was sieved and demagnetized to obtain a nickel-cobalt-aluminum precursor D1. According to the feed calculation, the chemical formula of the nickel-cobalt-aluminum precursor D1 is Ni 0.8 Co 0.15 Al 0.05 (OH) 2.05 , and its parameters are listed in Table 1.
[0174] The XRD test of NiCoAl precursor D1 was carried out, and the results are as follows Figure 2 As shown, Figure 2 There are only characteristic peaks of nickel-cobalt-aluminum hydroxide crystals, but no Al(OH) 3 The characteristic peaks of the crystal indicate that the nickel-cobalt-aluminum precursor does not have a two-phase structure.
[0175] The SEM test of NiCoAl precursor D1 was carried out, and the results are as follows Figure 4 As shown. Figure 4 As can be seen in the left figure, the precursor D1 contains relatively large particles with uneven particle distribution, which is an inherent defect of the traditional coprecipitation method for synthesizing nickel-cobalt-aluminum hydroxide precursors. Figure 4 As can be seen in the right figure, the spherical particles are stacked by lamellar primary particles, which is different from the nickel-cobalt-aluminum hydroxide precursor with a two-phase structure ( Figure 3 The right picture) is quite different.
[0176] Comparative Example 2
[0177] In order to compare the morphology of the nickel-cobalt hydroxide precursor and the nickel-cobalt-aluminum hydroxide precursor with a two-phase structure, the nickel-cobalt hydroxide precursor D2 was synthesized by coprecipitation method:
[0178] (1) 21.97 kg of NiSO 4 6H 2 O and 4.54 kg of CoSO 4 7H 2 O was dissolved in deionized water to prepare a mixed metal salt solution with a total volume of 50 L and a total metal ion concentration of 2.0 mol / L;
[0179] 8.4 kg of sodium hydroxide was added to deionized water to prepare 35 L of a first alkaline solution with a concentration of 6 mol / L;
[0180] Add 25% concentrated ammonia water into deionized water to prepare a 15% ammonia water solution;
[0181] (2) adding 3 L of deionized water into a reactor with a volume of 10 L, adding a portion of the first alkali solution and a portion of the ammonia solution as a reaction base solution into the reactor under stirring, and the stirring power density of the solution is 5 W / L;
[0182] The pH value of the reaction solution was 11.0 when the temperature was 50°C. 3 The concentration is 5g / L;
[0183] (3) under stirring conditions, adding the mixed metal salt solution prepared in step (1), another part of the first alkali solution and another part of the ammonia solution into the reactor in parallel to carry out a first contact reaction at a temperature of 60° C. and a stirring power density of the slurry of 9 W / L;
[0184] The addition time of the mixed metal salt solution, another part of the first alkali solution and another part of the ammonia solution is 130 hours;
[0185] In the slurry in the reactor, the addition rate of ammonia solution was adjusted so that NH 3 The concentration is 5 g / L, and the addition rate of the first alkaline solution is adjusted so that the pH value of the slurry measured at a liquid temperature of 50° C. is 11.0;
[0186] When the total volume of the material in the reactor reaches 8L, start the diaphragm pump and the concentrator to concentrate the slurry, the concentrated liquid flows back to the reactor, and the clear liquid is discharged into the waste liquid tank;
[0187] When the reaction time is the same as step (3) of Example 1, the feeding is stopped to obtain a second material;
[0188] (4) adding the second material into a washing machine, washing with deionized water, a sodium hydroxide solution with a mass fraction of 1%, and deionized water in sequence until the pH value of the washing liquid is below 8.0 (test value at 25° C. standard atmospheric pressure), stopping washing, and obtaining a third material;
[0189] (5) The third material is dried at 120° C. for 10 h. After drying, it is sieved and demagnetized to obtain a nickel-cobalt precursor D2. According to the calculation of the feed, the chemical formula of the nickel-cobalt precursor D2 is Ni 0.84 Co 0.16 (OH) 2 , and its parameters are listed in Table 1.
[0190] The SEM test of nickel-cobalt precursor D2 was carried out, and the results are as follows Figure 5 As shown. Figure 5 (Left Figure) shows that the precursor D2 particles are evenly distributed and do not contain small particles; Figure 5 As can be seen from the figure (right), the spherical particles are stacked by lamellar primary particles, which is different from the nickel-cobalt-aluminum hydroxide precursor with a two-phase structure ( Figure 3 The right picture) is quite different.
[0191] Table 1
[0192]
[0193] Preparation Examples 1-3
[0194] The nickel-cobalt-aluminum-lithium ternary materials A1-1 to A3-1 are prepared by the following steps:
[0195] S1. LiOH·H 2 O is ball-milled and mixed with a nickel-cobalt-aluminum hydroxide precursor having a two-phase crystal structure for 3 h to obtain a first product;
[0196] S2. Calcinate the first product in an oxygen atmosphere for 15 hours to obtain nickel cobalt aluminum lithium ternary materials A1-1 to A3-1, wherein the calcination temperature for synthesizing A1-1 is 750°C, the temperature for synthesizing A2-1 is 770°C, and the temperature for synthesizing A3-1 is 660°C. The physical and chemical properties and electrochemical properties of the materials are tested, and the test results are listed in Table 2.
[0197] Preparation Comparative Example 1
[0198] The nickel cobalt aluminum oxide lithium ternary material D1-1 was prepared by the method of Example 1, and the parameters are listed in Table 2. The difference is that the nickel cobalt aluminum precursor D1 of Comparative Example 1 was used as the precursor material, the calcination temperature was 750°C, and the physicochemical and electrochemical properties of the material were tested. The test results are listed in Table 2.
[0199] Preparation Comparative Example 2
[0200] S1. LiOH·H 2 O, nickel cobalt hydroxide precursor D2 and aluminum hydroxide are ball-milled and mixed (the feed ratio is set according to the element ratio in the product) for 3 hours to obtain the first product;
[0201] S2. The first product was calcined in an oxygen atmosphere for 15 hours to obtain nickel cobalt aluminum oxide lithium ternary material D2-1, wherein the calcination temperature was 750°C. The material was tested for physical and chemical properties and electrochemical properties. The test results are listed in Table 2.
[0202] XRD tests were performed on the prepared nickel cobalt aluminum lithium ternary materials A1-1, D1-1, and D2-1, and the results are as follows: Figure 7 As shown in the figure, it can be seen that the XRD curves of A1-1 and D1-1 are LiNiCoAlO 2 The single-phase structure does not contain impurity peaks. In the XRD curve of sample D2-1, β-LiAlO2 phase, indicating that the Al element can be dispersed into the crystal structure to form a single crystal structure phase in the nickel cobalt aluminum oxide ternary material prepared by the nickel cobalt aluminum precursor prepared by the method disclosed in the present invention.
[0203] Test Case
[0204] The steps of preparing a lithium ion battery using the nickel cobalt aluminum oxide ternary material of the above-mentioned preparation example and the preparation comparative example are as follows:
[0205] Accurately weigh the positive electrode materials A1-1 to A3-1, D1-1 and D2-1, the conductive agent and PVDF in a mass ratio of 8:1:1, add the three materials to NMP, and stir to make a slurry. Spread the stirred slurry on a 16μm thick aluminum foil and dry it at 110℃ for 30min. Roll the dried electrode sheet and punch it into an electrode sheet with a diameter of φ12 with a punching machine. Dry the electrode sheet in a vacuum oven at 120℃ for 12h. The surface density of the electrode sheet is about 100g / m 2 .
[0206] In an argon atmosphere glove box, the Li sheet was used as the negative electrode, the electrode sheet prepared above was used as the positive electrode, and 1 mol / L LiPF 6 The EC / EMC / DMC solution is used as the electrolyte, and PP / PE polymer separator is used to assemble into a CR2032 button half-cell.
[0207] The prepared battery was subjected to electrical performance tests, and the results are listed in Table 2. The test conditions include: discharge capacity test conditions: charge and discharge voltage is 2.75-4.3V, charge and discharge rate is 0.1C, and test temperature is 25°C; during the cycle performance test, the charge and discharge rate is 0.5C.
[0208] Table 2
[0209]
[0210] According to the data in Table 1, the nickel-cobalt-aluminum precursor prepared by the method disclosed in the present invention has a higher tap density, a larger particle size and a suitable specific surface area, and the nickel-cobalt-aluminum lithium oxide ternary material prepared by the method has a larger tap density and particle size, and has good electrochemical properties, especially a better capacity retention rate.
[0211] The preferred embodiments of the present disclosure are described in detail above in conjunction with the accompanying drawings; however, the present disclosure is not limited to the specific details in the above embodiments. Within the technical concept of the present disclosure, a variety of simple modifications can be made to the technical solution of the present disclosure, and these simple modifications all fall within the protection scope of the present disclosure.
[0212] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present disclosure will not further describe various possible combinations.
[0213] In addition, various embodiments of the present disclosure may be arbitrarily combined, and as long as they do not violate the concept of the present disclosure, they should also be regarded as the contents disclosed by the present disclosure.
Claims
1. A nickel-cobalt-aluminum precursor having a two-phase structure, characterized in that: The nickel-cobalt-aluminum precursor includes secondary particles containing nickel-cobalt hydroxide and Al(OH) 3.
2. The nickel-cobalt-aluminum precursor according to claim 1, wherein The nickel-cobalt hydroxide has a β crystal form; The chemical formula of the nickel cobalt hydroxide is Ni 1-x Co x (OH)2, 0.05≤x≤0.
2.
3. The nickel-cobalt-aluminum precursor according to claim 1, wherein In the XRD spectrum of the nickel-cobalt-aluminum precursor, there are characteristic peaks of Al(OH)3 crystals and characteristic peaks of nickel-cobalt hydroxide crystals.
4. The nickel-cobalt-aluminum precursor according to claim 1, wherein The secondary particles have a two-phase microscopic crystal structure in which Al(OH) 3 crystals are dispersed in nickel cobalt hydroxide crystals.
5. The nickel-cobalt-aluminum precursor according to claim 1, wherein The tap density of the secondary particles is 1.90 g / cm 3 Above, the specific surface area is 6-25m 2 / g, D50 is 8-15μm.
6. The nickel-cobalt-aluminum precursor according to claim 1, wherein In the nickel-cobalt-aluminum precursor, the molar ratio of aluminum element to metal element is (0.02-0.09):
1.
7. A method for preparing a nickel-cobalt-aluminum precursor having a two-phase structure, characterized in that: The method comprises: under stirring conditions, subjecting a first material containing a nickel source, a cobalt source and Al(OH)3 nanoparticles, a first alkaline solution and an ammonia solution to a first contact reaction; The D50 of the Al(OH)3 nanoparticles is 10-50nm; The first contact reaction is carried out under the condition that the pH value measured at a liquid temperature of 50° C. is 10.5-11.
0.
8. The method according to claim 7, wherein: The method for preparing the first material comprises: mixing a suspension containing the Al(OH)3 nanoparticles with a solution containing the nickel source and the cobalt source under stirring; Optionally, the solid content of the suspension is 10-30% by weight; Optionally, the total concentration of cobalt ions and nickel ions in the solution is 1.5-2.5 mol / L; Optionally, in the first material, the molar ratio of aluminum element to metal element is (0.02-0.09):
1.
9. The method according to claim 7, wherein: The nickel source includes nickel sulfate and / or nickel chloride; The cobalt source includes cobalt sulfate and / or cobalt chloride.
10. The method according to claim 7, wherein: The first alkaline solution contains sodium hydroxide and / or potassium hydroxide; The concentration of the first alkaline solution is 4-10 mol / L, and the mass fraction of the ammonia solution is 15-22%.
11. The method according to claim 7, wherein: The method comprises the following steps: a. Add water, a portion of the first alkaline solution and a portion of the ammonia solution into a reaction kettle under stirring; The total volume of the water, a portion of the first alkaline solution and a portion of the ammonia solution accounts for 30-80% of the volume fraction of the reactor; b. Adding the first material, another part of the first alkali solution and another part of the ammonia solution into the reactor of step a under stirring to carry out the first contact reaction, and stopping feeding when the D50 of the solid material in the reactor is 8-15 μm; The first material, another part of the first alkaline solution and another part of the ammonia solution are added for 80-200 hours; When the volume of the material in the reactor accounts for 80%-85% of the total volume of the reactor, the clear liquid is discharged out of the reactor through a concentrator.
12. The method according to claim 11, wherein: In step a, in the solution in the reactor, the concentration of NH3 is 3-10 g / L, the pH value of the solution in the reactor is 10.5-11.0 measured at a liquid temperature of 50° C., and the stirring power density of the solution is 3-9 W / L; In step b, the concentration of NH3 in the slurry in the reactor is 3-10 g / L; the pH value of the slurry in the reactor is 10.5-11.0 measured at a liquid temperature of 50° C., and the stirring power density of the slurry is 3-9 W / L; The temperature of the first contact reaction is 50-65°C.
13. The method according to claim 7, wherein: The method further includes: performing alkaline washing on the second material obtained by the first contact reaction, wherein the alkaline washing includes: washing the second material with water, a second alkaline solution and water in sequence until the pH value of the washing solution is below 8.0; The second alkaline solution contains sodium hydroxide and / or potassium hydroxide, the concentration of the second alkaline solution is 1-2% by weight, and the total time of the alkaline washing is 1-3 hours; Optionally, the method further comprises: drying the third material obtained by the alkali washing, and the conditions of the drying process comprise: a time of 5-12 hours and a temperature of 100-150°C.
14. A nickel-cobalt-aluminum precursor having a two-phase structure prepared by the method according to any one of claims 7 to 13.
15. A method for preparing a nickel-cobalt-aluminum-lithium ternary material, characterized in that: The method includes: The nickel-cobalt-aluminum precursor of any one of claims 1 to 6 and 14 is mixed with a lithium source and then heat-treated in an oxygen-containing atmosphere.
16. The method according to claim 15, wherein: The lithium source includes one or more of lithium carbonate, lithium hydroxide, lithium acetate, lithium oxalate and lithium nitrate; The molar ratio of the lithium source calculated as lithium element to the nickel-cobalt-aluminum precursor calculated as metal element is (1.01-1.06):1; Optionally, the mixing method is solid phase ball milling, and the solid phase ball milling time is 1-5 hours.
17. The method according to claim 15, wherein: The heat treatment conditions include: time of 8-20 hours and temperature of 650-850°C.
18. Nickel-cobalt-aluminum-lithium ternary material prepared by the method according to any one of claims 15 to 17.
19. The nickel-cobalt-aluminum-lithium ternary material according to claim 18, wherein: The tap density of the nickel-cobalt-aluminum-lithium oxide ternary material is 2.3 g / cm 3 Above, D50 is 8-15μm.
20. A lithium ion battery, comprising a positive electrode, an electrolyte and a negative electrode, characterized in that: The positive electrode comprises the nickel cobalt aluminum oxide lithium ternary material as described in claim 18 or 19.
Citation Information
Patent Citations
A method for preparing lithium nickel cobalt aluminum oxide cathode material
CN111777103B